Persepsi Dan Perilaku Konsumen Di Jakarta Terhadap Logo “Pilihan Lebih Sehat” Pada Pangan Olahan - Siti Maemunah; Tety Herawaty (Badan Pengawas Obat dan Makanan, 2025)
Non-communicable diseases pose a major global mortality threat, with an estimated 15 million people aged 30–70 dying annually due to these conditions. One contributing factor is the excessive consumption of processed foods high in sugar and salt. Nutritional information on processed foods serves as an alternative to help consumers make dietary choices aligned with their nutritional needs. The “Healthier Choice” logo is a government initiative designed to protect consumers. However, research on the “Healthier Choice” logo has not been conducted in Indonesia. This study aimed to examine consumer perceptions and behaviors regarding the use of the “Healthier Choice” logo on processed foods. A survey was conducted with 63 subjects in Jakarta, predominantly aged 24–54 years (85.7%) and holding higher education degrees (84.1%). The results indicated that 54% of respondents had positive perceptions and 68.3% exhibited favorable behaviors toward the logo. Correlation analysis by residential area in Jakarta showed that only North Jakarta had a negative perception below 50% (33.3%), whereas 71.4% of respondents in East Jakarta reported positive perceptions. Regarding behavior, at least 50% of respondents in all Jakarta regions demonstrated good practices in response to the logo. Bivariate analysis by age revealed that most respondents aged 25–54 had positive perceptions (74.1%) and positive behaviors (59.3%) toward the logo. These findings suggest that consumers support the implementation of the “Healthier Choice” logo. Further research is needed to explore consumer perceptions and behaviors regarding the logo with more diverse respondent characteristics, including residential area and educational background.